Eurosklerose? - Ganßmann, Heiner; Haas, Michael (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 1999)
Conservative critics of European economic policies argue that high and persistent European unemployment is caused by institutional rigidities which are traced back to welfare states and union strength. By contrast, low US unemployment is attributed to high labour market flexibility. These claims are examined. The high social costs of US style flexibility in terms of income inequality and poverty suggest that the „cure“ for high unemployment should be sought elsewhere, namely by relying on policies - as in the Netherlands and Denmark - which combine high levels of social security with increased labour market flexibility.